INVOLVING STUDENTS IN PROJECTING AND CREATING ELECTRONIC EDUCATIONAL ENVIRONMENTS IN PHYSICS AS A WAY OF THEIR PERSONALITY-ORIENTED TRAINING FOR METHODICAL ACTIVITY - V. D. Sharko (Ìнформаційні технології в освіті)
The article reveals the possibilities of training future teachers of Physics for methodical activity by involving them in projecting and creating electronic information&communicationeducational environments (EICEE) in the school course in Physics. The author defines priority directions of teacher’s activity in teaching Physics from the standpoint of the competence approach to measuring quality of physical education.They are characterized according to modern requirements. The main types of learners’ activities in Physics (theoretical material acquisition, solving various types of physical problems, making physical experiments, carrying out research)are represented in the context of the competence approach to organization of educational process. The author reveals the essence and structure of the notion of “electronic information&communicationeducational environment”according to normative and didactic requirements.Integrated model of technology of personality-oriented training of future teachers of Physics for methodical activity is suggested. An algorithm of teacher’s and student’s actions for projecting and creating electronic information&communicationeducational environment as a type of teacher’s methodical activity is given. The advantages of personality-oriented technology of professional training of future teachers of Physics from the standpoint of individual, activity and competence approaches are defined.